Efektivitas Kombinasi Ekstrak Kulit Pisang Kepok dan Minyak Cengkeh sebagai Obat Kumur Herbal Penghambat Pertumbuhan Streptococcus mutans: Effectiveness of the Combination of Kepok Banana Peel Extract and Clove Oil as a Herbal Mouthwash in Inhibiting Streptococcus mutans Growth - Lyrra Mirna Amanda; Cicik Wijayanti; Nabilah Rosdiana Maulana; Yuke Pramudita Sari; Ali Abraham; Khoirul Ngibad (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2025)
Streptococcus mutans is one of the bacteria that causes teeth disorders. This bacterium is a typical gram-positive, round-shaped bacteria often found in pairs or chains. This study aims to determine the performance of the combination of kepok banana peel extract and clove oil as an herbal mouthwash formulation that inhibits the growth of Streptococcus mutans bacteria. The method carried out in this study is an experimental method using the disc diffusion method. The components of the three formulations designed, formulation I, use 1 gram of kepok banana peel extract and 5 ml of clove oil. In formulation II, 2 grams of kepok banana peel extract and 7.5 ml of clove oil were used, while in formulation III, 3 grams of kepok banana peel extract and 10 ml of clove oil were used. The evaluation test of mouthwash preparations is carried out several times, including organoleptic tests. The study included antibacterial activity tests. In this study, the results of the antibacterial activity test of herbal mouthwash formulations were obtained to have inhibitory power in Streptococcus mutans. The inhibition zone produced by formulation I was 13.38 mm (strong), formulation II was 11.64 mm (strong), and formulation III was 10.55 mm (strong). Based on research, it can be concluded that this herbal mouthwash formulation has the potential as a natural alternative in controlling Streptococcus mutans and preventing oral diseases. Keywords: 96% ethanol extract; Kepok banana peel; Clove oil; Streptococcus mutans.